A aplicação dos royalties da usina hidrelétrica de Itaipu Binacional como recurso de desenvolvimento aos municípios da zona de fronteira entre Brasil e Paraguai - Girotto, Nilse Lúcia (2019)
This dissertation has as its research plan the historical study of the agreements and treaties for the implementation of the largest binational architectural project between Brazil and Paraguay, the use of the Paraná River waters with the construction of the Itaipu Binacional Hydroelectric Power Plant. Its construction caused intense changes of economic, social, environmental and territorial order. The main objective of this work is to analyze the impacts of the installation of the Itaipu Plant and the payment of royalties as compensation for the negative externalities for the Brazilian and Paraguayan municipalities affected by the project. The main bias is the analysis of the application of the funds received in the form of compensation, discussing whether they achieved the objective of minimizing the impacts arising from the construction of the megaproject and to what extent they boosted regional economic development. The theoretical framework was based on concepts and theories related to the themes of development discourse, megaprojects, the transformation of space and the receipt of royalties as a way of compensating for the flooding of land. The methodology used involved bibliographic research, documentary research and interview. Fieldwork and information gathering allowed us to emphasize the importance that the transfer of royalties represents for the Brazilian and Paraguayan municipal financial revenues and to measure the effectiveness of the application of these resources as a driver for raising social indicators. We highlight the importance of discussing the current moment of political articulation in the formation of study groups, commissions and debates prior to the revision of Annex C to the Itaipu Treaty, scheduled for 2023, which includes the financial base of the Itaipu Plant and supports the payment of royalties to the affected parties.